Phytochemical Properties, In Silico and In Vitro Analysis of the Antibacterial Activity of Cinnamomum sulavesianum Bark from Sulawesi - Hurria; Alfian, Anggra; Mahmudah, Rifa’atul (Research Center of Inorganic Materials and Coordination Complexes, FMIPA Universitas Sriwijaya, 2026)
Cinnamomum sulavesianum is an aromatic plant in Sulawesi, exhibiting significant potential as an antibacterial candidate. The ongoing search for new antibacterial agents, particularly from natural sources, is crucial due to the rising antibiotic resistance. This study aims to identify the essential oil composition of C. sulavesianum and evaluate its antibacterial properties in silico and in vitro. This study represents the first report on the essential oil content of C. sulavesianum bark and its associated antibacterial effects. The analysis of essential oil content was conducted using Gas Chromatography-Mass Spectrometry (GC-MS) with an Agilent Technologies 7890 Gas Chromatograph equipped with an Auto Sampler. The in silico analysis has been performed through molecular docking of compounds found in C. sulavesianum. Antibacterial testing was carried out using the disc diffusion method, targeting bacteria such as Staphylococcus aureus, Staphylococcus epidermidis, Escherichia coli and Pseudomonas aeruginosa. The results from the GC-MS analysis revealed that the bark of C. sulavesianum consists of 10 essential oil compounds, with the primary constituents being Linalool (32.3%), Copaene (6.77%), Eugenol (5.05%), and Eucalyptol (3.17%). In silico evaluations suggest these compounds possess antibacterial potential against gram-positive and gram-negative pathogenic bacteria. Furthermore, in vitro assessments demonstrated that the bark extract of C. sulavesianum formed an inhibition zone that was, on average, categorized as strong based on its inhibitory efficacy. These findings indicate that C. sulavesianum bark holds promise for developing new antibiotics.